1986
DOI: 10.1161/01.cir.73.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection during transient coronary artery occlusion in man: beneficial effects of regional beta-adrenergic blockade.

Abstract: The goal of this study was to verify whether myocardial protection could be achieved via the intracoronary administration of propranolol in patients undergoing percutaneous transluminal coronary angioplasty (PTCA). Accordingly, 21 patients undergoing PTCA were randomly assigned to receive either intracoronary placebo (group A, n = 10) or intracoronary propranolol (group B, n = 11). Three balloon inflations (i.e., coronary artery occlusions) were performed in each patient. Inflations I and II (maximum duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…[17][18][19][20] Human studies have demonstrated that IC propranolol before transient coronary artery occlusion can delay the onset and severity of myocardial ischemia as detected by surface electrocardiography without decreasing heart rate or blood pressure. 11,12 The present study demonstrates that IC ␤-blocker can also protect against myocardial injury in this setting. We propose that the effects of microembolization during PCI are often transient and that reperfusion of small myocardial areas occurs after dissolution of these microemboli.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…[17][18][19][20] Human studies have demonstrated that IC propranolol before transient coronary artery occlusion can delay the onset and severity of myocardial ischemia as detected by surface electrocardiography without decreasing heart rate or blood pressure. 11,12 The present study demonstrates that IC ␤-blocker can also protect against myocardial injury in this setting. We propose that the effects of microembolization during PCI are often transient and that reperfusion of small myocardial areas occurs after dissolution of these microemboli.…”
Section: Discussionsupporting
confidence: 54%
“…Propranolol at a dose of 15 g/kg 12 or 0.9% NaCl (placebo) was injected into the coronary artery through the dilatation catheter, the distal tip of which was positioned across the stenosis or stenoses (if more than 1 site underwent PCI). The study drug was thus delivered directly into the myocardial region supplied by the stenotic coronary artery undergoing PCI.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…This could not be evaluated in this protocol, but could better be studied by direct coronary injection into the affected left ventricular region. 6 In addition, we studied responses after only one fixed dose of intravenous propranolol designed to produce fl-blockade in most patients. Even more patients may have benefited if multiple incremental doses had been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-blockers, administered intravenously or intracoronarily, diminish ischemia during acute coronary occlusion in humans [12,13]. Bonnier et al [14] showed that a calcium entry blocker, diltiazem, could reduce oxypurine production from high-energy phosphates, induced by percutaneous transluminal coronary angioplasty (PCTA).…”
mentioning
confidence: 99%